Analýza a návrh informačního systému pro firmu eSports.cz, s.r.o. - Kobelka, Michal (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Diplomová práce se zabývá analýzou a návrhem informačního systému pro firmu eSports, s.r.o. První kapitola předkládá teoretická východiska nutná k pochopení celé problematiky. Druhá kapitola posuzuje současný stav společnosti eSports, s.r.o. a analyzuje hlavní firemní procesy. V poslední kapitole jsou předloženy návrhy datového modelu nového informačního systému.

The master's thesis deals with analysis and design of information system for company eSports, s.r.o. First chapter presents theoretical basis which is necessary for understanding the problem. Second chapter assesses current situatuion of eSports, s.r.o. and analyzes main processes of the company. Last chapter provides proposals for data model of new information system.
The Design of Information System for Company eSport.cz, s.r.o.
Keywords: datový model; informační systém; návrh databáze; MySQL; procesní analýza; data model; information system; database design; MySQL; process analysis